1995
DOI: 10.1002/1097-0142(19950215)75:4<968::aid-cncr2820750411>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of a 75-mg/m2 dose of docetaxel with prednisone premedication for patients with advanced non-small cell lung cancer

Abstract: Background. A prior Phase II study of a 100‐mg/m2 dose of docetaxel conducted at the Memorial Sloan‐Kettering Cancer Center (New York, NY) demonstrated a 38% response rate with grade 3 or 4 neutropenia in 76% of the patients and a grade 2 or greater rash or infusion‐related reaction in 41% and 34% of the patients, respectively. The current Phase II study sought to determine the activity of a 75‐mg/m2 dose of docetaxel to establish whether this lower dose, combined with prednisone, ameliorates toxicity. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…Based on these phase I studies, the recommended singleagent dose and schedule for docetaxel was 100 mg m-2 given as a 1-h infusion every 3 weeks. Phase II studies on docetaxel showed activity in breast cancer (Seidman et al, 1993;Ten Bokkel-Huinink et al, 1994;Trudeau et al, 1993;Valero et al, 1993;Chevallier et al, 1995), non-small-cell lung cancer (Cemy et al, 1994;Fossella et al, Rotterdam, Groene Hilledijk 301, 3075 EA Rotterdam, The Netherlands 1995; Miller et al, 1995), head and neck cancer , gastric cancer (Sulkes et al, 1994), melanoma (Aamdal et al, 1994), soft tissue sarcoma (Van Hoesel et al, 1994) and pancreatic cancer (De Fomi et al, 1994). The most important side-effect was an early and short-lasting neutropenia, which in 20% of the patients was complicated by infection (Pronk et al, 1995).…”
mentioning
confidence: 99%
“…Based on these phase I studies, the recommended singleagent dose and schedule for docetaxel was 100 mg m-2 given as a 1-h infusion every 3 weeks. Phase II studies on docetaxel showed activity in breast cancer (Seidman et al, 1993;Ten Bokkel-Huinink et al, 1994;Trudeau et al, 1993;Valero et al, 1993;Chevallier et al, 1995), non-small-cell lung cancer (Cemy et al, 1994;Fossella et al, Rotterdam, Groene Hilledijk 301, 3075 EA Rotterdam, The Netherlands 1995; Miller et al, 1995), head and neck cancer , gastric cancer (Sulkes et al, 1994), melanoma (Aamdal et al, 1994), soft tissue sarcoma (Van Hoesel et al, 1994) and pancreatic cancer (De Fomi et al, 1994). The most important side-effect was an early and short-lasting neutropenia, which in 20% of the patients was complicated by infection (Pronk et al, 1995).…”
mentioning
confidence: 99%
“…Dose reduction according to body surface area does not necessarily lead to less toxicity. In fact, one trial has shown that a reduction of dose to 75 mg/m 2 had little effect on the incidence or severity of neutropenia (21). This is not surprising considering the known wide interpatient variability of pharmacokinetics of most cytotoxics.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators at Memorial Sloan-Kettering Cancer Center also evaluated a slightly lower dose of docetaxel (75 mg/m 2 ) in an attempt to lower toxicity. 53 In all studies, the principal toxicity proved to be myelosuppression, although rash and fluid retention were common. Hypersensitivity reactions or allergic reactions were also common but rarely precluded treatment.…”
Section: Docetaxelmentioning
confidence: 99%
“…However, investigators at Memorial Sloan-Kettering Cancer Center recommend using the higher docetaxel dose in future NSCLC studies. 53 This recommendation was made largely because the toxicity of the lower dose of docetaxel (75 mg/m 2 ) was comparable to that of the higher dose (100 mg/m 2 ) in their hands. Japanese investigators have found lower doses of 60 mg/m 2 yield response rates in breast cancer equivalent to that achieved with the higher docetaxel doses.…”
Section: Docetaxelmentioning
confidence: 99%